Assessing the Impact of Climate Change on Sediment Loads in a Large Mediterranean Watershed. Issue 7 (July 2016) - Nerantzaki, Sofia D.; Giannakis, Georgios V.; Nikolaidis, Nikolaos P.; Zacharias, Ierotheos; Karatzas, George P.; Sibetheros, Ioannis A.
Abstract : Abstract: Acheloos is the second longest and the largest, in terms of discharge, native river in Greece, supplying three hydroelectric dams along its route. The Kremasta dam, which forms the largest artificial lake in Greece, is the first dam fed by Acheloos and two other rivers. Sediment accumulation in such large reservoirs is of major concern, as it reduces storage capacity and hydropower production. In this study, the reservoir is utilized as a live record of constantly renewed sediment deposition data, which is used as a means of assessing the accumulated sediment loads originating from the watershed. The Soil and Water Assessment Tool model was combined with data from previous field surveys, which estimated the volume of deposited sediments in the reservoir. After modeling the discharge of three rivers into the Kremasta reservoir using available monthly field data from 1965 to 2001, the Soil and Water Assessment Tool was successfully calibrated against the deposited sediment mass data, accumulated at the reservoir during the first 34 years of its operation. Simulation results for a set of International Panel on Climate Change "A1B" climate change scenarios suggested a 14.6% decrease in the average rainfall on the watershed, between the 2016–2055 and 2056–2095 time periods, which induces a proportional (19.5%) decrease in flow and a milder (7.9%) decrease in the deposited sediment mass. It was also estimated that by the year 2100 the deposited sediment volume will occupy 6.1% of the effective volume of the reservoir, a value much lower than the estimated dead volume of the dam (17.4%).